2016
DOI: 10.1097/mpa.0000000000000477
|View full text |Cite
|
Sign up to set email alerts
|

The Atlanta Classification, Revised Atlanta Classification, and Determinant-Based Classification of Acute Pancreatitis

Abstract: The RAC and DBC were generally comparable in stratifying severity. The paucity of patients in the critical category in the DBC limits its utility. Neither classification accounts for the impact of multisystem POF, which was the strongest predictor of mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 18 publications
4
26
0
2
Order By: Relevance
“…This is in agreement with many prior studies that have indicated that both the RAC and the DBC strongly predict length of hospital stay better than OAC without any significant differences between them [9,10,22]. Further, while little work has been done to assess the predictive capacity of BISAP and PANC 3 on LOS, both systems have been shown to have predictive capacity at identifying severe AP as defined by RAC and DBC [4,17,19]; so it logically follows that their predictive capacity at identifying the length of stay should be similar to RAC and DBC.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…This is in agreement with many prior studies that have indicated that both the RAC and the DBC strongly predict length of hospital stay better than OAC without any significant differences between them [9,10,22]. Further, while little work has been done to assess the predictive capacity of BISAP and PANC 3 on LOS, both systems have been shown to have predictive capacity at identifying severe AP as defined by RAC and DBC [4,17,19]; so it logically follows that their predictive capacity at identifying the length of stay should be similar to RAC and DBC.…”
Section: Discussionsupporting
confidence: 82%
“…Both these 2 systems classify AP after at least 48 h of admission using complications such as organ failure and local complications to determine severity. Both have been shown to be more effective than OAC at stratifying in terms of severity [7][8][9][10]. However, since at least 48 h are required, these systems are more useful for classifying disease severity than predicting it.…”
Section: Introductionmentioning
confidence: 99%
“…Every patient in our study underwent pancreatic imaging. AP was divided into 3 degrees based on severity: mild, moderately severe, and severe acute pancreatitis, according to the Atlanta Classification 2012 revision [2,11,12]. Patients diagnosed with MAP had an absence of organ failure and local/systemic complications.…”
Section: Methodsmentioning
confidence: 99%
“…[16][17][18] Patients who are transferred to hospitals represent a population of severely ill patients with a higher morbidity and mortality than those who are directly admitted to a hospital. 31,[33][34][35][36] Extrapancreatic Necrosis Overall, the prevalence of persistent organ failure is 4% among patients directly admitted to a hospital compared with 26% to 39% when transferred patients are included in the data.…”
Section: Persistent Organ Failurementioning
confidence: 99%